2003
DOI: 10.1029/2003gl017391
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Pn velocity and anisotropy structure beneath the Anatolian plateau (eastern Turkey) and the surrounding regions

Abstract: We use Pn phase travel time residuals to invert for mantle lid velocity and anisotropy beneath northern Arabia‐eastern Anatolia continent‐continent collision zone. The primary phase data were obtained from the temporary 29‐station broadband PASSCAL array of the Eastern Turkey Seismic Experiment. These data were supplemented by phase data from available stations of the Turkish National Seismic Network, the Syrian National Seismic Network, the Iranian Long Period Array, and other stations around the southern Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 23 publications
8
89
1
Order By: Relevance
“…Data recorded via these stations of this project have been used and processed by many authors with different methods , 2004Gök et al, 2003Gök et al, , 2007Sandvol et al, 2003a;Türkelli et al, 2003;Zor et al, 2003;Angus et al, 2006;Lei and Zhao, 2007;Özacar et al, 2008;Zor, 2008;Biryol et al, 2011;Gökalp, 2012;Delph et al, 2015b) and they have supplied new approaches for the 3-D crust and mantle dynamics of the region. Al-Lazki et al (2003) interpreted low (<7.8 km/s) Pn velocities under the Anatolian Plateau as most likely the absence of the mantle lid, just as AlLazki et al (2004) observed the same velocities at the broad-scale in eastern Turkey and surrounding regions associated with hot, unstable mantle lid zones and active volcanism starting from the Late Miocene. In addition, due to unobservable S n velocities in eastern Turkey, Gök et al (2003) stated that asthenospheric upwelling brings about a lack of lithospheric mantle and this may be associated with Keskin's model (2003), while Gök et al (2007), using receiver function modeling and surface wave group velocities, found extremity S/L g waves attenuation for the East Anatolian Plateau, which is supported by asthenospheric material.…”
Section: Introductionmentioning
confidence: 90%
“…Data recorded via these stations of this project have been used and processed by many authors with different methods , 2004Gök et al, 2003Gök et al, , 2007Sandvol et al, 2003a;Türkelli et al, 2003;Zor et al, 2003;Angus et al, 2006;Lei and Zhao, 2007;Özacar et al, 2008;Zor, 2008;Biryol et al, 2011;Gökalp, 2012;Delph et al, 2015b) and they have supplied new approaches for the 3-D crust and mantle dynamics of the region. Al-Lazki et al (2003) interpreted low (<7.8 km/s) Pn velocities under the Anatolian Plateau as most likely the absence of the mantle lid, just as AlLazki et al (2004) observed the same velocities at the broad-scale in eastern Turkey and surrounding regions associated with hot, unstable mantle lid zones and active volcanism starting from the Late Miocene. In addition, due to unobservable S n velocities in eastern Turkey, Gök et al (2003) stated that asthenospheric upwelling brings about a lack of lithospheric mantle and this may be associated with Keskin's model (2003), while Gök et al (2007), using receiver function modeling and surface wave group velocities, found extremity S/L g waves attenuation for the East Anatolian Plateau, which is supported by asthenospheric material.…”
Section: Introductionmentioning
confidence: 90%
“…Slab breakoff leads to the generation of a shallow thermal perturbation and opening of an asthenospheric window that in turn caused partial melting of the subduction metasomatized lithospheric mantle beneath the collision zone (Davies & von Blanckenburg 1995). The findings of the recent northern part of UDMA (TaghizadehFarahmand 2010) and eastern Turkey seismic experiment (Al-Lazki et al 2003;Gök et al 2003;Zor et al 2003) and seismic velocity from the Zagros collision to UDMA and CIM (Kaviani et al 2007), along with the tomographic models, suggest that velocity difference at shallow depth is due to higher mantle temperatures and/or higher fluid content beneath NW Iran and eastern Turkey. These observations, combined with trace element and isotope characteristics of these volcanic sequences, suggest that their magmas were derived from partial melting of subduction-metasomatized continental lithospheric mantle in the spinel-peridotite field beneath the CIM.…”
Section: Geodynamic Implicationsmentioning
confidence: 99%
“…Recent seismic data (Al-Lazki et al, 2003;Gök, Türkelli, Sandvol, Seber, & Barazangi, 2000) suggested that either there is no lithospheric mantle in the region or, otherwise, it is relatively thin. With respect to recent geophysical research (Barazangi et al, 2006;Keskin, 2003;Şengör et al, 2003;Zor et al, 2003) in this region, the fraction in the lithospheric mantle is thought to be at the depth of 45-50 km.…”
Section: Evolution Modelmentioning
confidence: 99%